Monitoração de vibrações de estruturas com o emprego de sensores em fibra óptica - Silva, Jean Carlos Cardozo da (2005)
This work deals with the analysis of perspectives of dynamic study in structures using a sensor system based on fibre optic Bragg gratings. The understanding of vibrations in structures enables the development of new materials, and of new design concepts that improves the sizing and security in engineering projects. The vibration measurements are carried out with a fibre optic Bragg grating demodulation system. The system has a low cost and easiness of implementation when compared to other available instruments. The output range signal of the instrument is between 0 V to 5 V, compatible to standard PC interfacing systems. The results show that the system is able to monitor vibrations in different types of materials, such as wood, steel, reinforced concrete and bone. The sensor is compared to commercial sensors (strain gauges and accelerometer). Beyond of civil structure, studies have been carried out to develop a technique, in vitro, to evaluate a new dental implant concept. The modal analysis techniques employed in the characterization of the different structures studied show the necessity of instrumentation able to measure low amplitude signals with high signal noise ratio. These characteristics are considered essential in material degradation studies by modal analysis technique.